Vitamin D(3) Supplementation and Antibiotic Consumption – Results from a Prospective, Observational Study at an Immune-Deficiency Unit in Sweden - Norlin, Anna-Carin (PLoS One, 2016)
BACKGROUND: Vitamin D supplementation has been proposed to improve clinical symptoms during respiratory tract infections (RTIs), but results from randomized, placebo-controlled trials (RCT) are inconclusive. Previously, we performed an RCT in patients with various immune-disorders and observed that supplementation with 4000 IU vitamin D/day during 12 months significantly reduced antibiotic consumption and RTIs. This formed the basis for new guidelines at our unit; i.e. patients with insufficient levels of 25-hydroxyvitamin D (≤75 nmol/L) are now offered vitamin D supplementation. The aim of this prospective follow-up study was to evaluate the outcome of these new recommendations with regard to antibiotic consumption in our unit. METHOD: 277 patients with insufficiency were supplemented with vitamin D(3), 1500–1600 IU/day for 12 months. Each patient was its own control and data on antibiotic consumption was monitored 12 months before and 12 months after initiation of vitamin D(3) supplementation. RESULTS: Vitamin D(3) supplementation resulted in a significantly reduced antibiotic consumption, from 20 to 15 days/patient (p<0.05). The number of antibiotic-free patients increased from 52 to 81 after vitamin D(3) supplementation; OR 1.79; 95% CI 1.20–2.66 (p<0.01). The number of antibiotic-prescriptions decreased significantly, a finding that mainly was attributed to a reduction of respiratory tract antibiotics (p<0.05). Subgroup analysis showed that only patients without immunoglobulin substitution (n = 135) had a significant effect of vitamin D supplementation. CONCLUSION: Vitamin D(3) supplementation of 1600 IE /day is safe to use in immunodeficient patients with 25-OHD levels less than 75 nmol/L and significantly reduced the antibiotic consumption in patients without immunoglobulin substitution.